Trusting me, trusting you - trusting technology? A multidisciplinary analysis to uncover the status quo of research on trust in technology - Bettina Distel; Katherine M. Engelke; Sydney Querfurth (Westfälische Wilhelms-Universität Münster, European Research Center for Information Systems (ERCIS), 2021)
[Conclusion] As far as we are aware, this study is one of the first to give a comprehensive overview of research on trust in the context of technology. It thus goes beyond previous studies that examine trust in the context of specific technologies in that it uncovers and structures the status quo of scientific research in this area, with a special focus on trust in technologies. Furthermore, this article contributes to current research by deriving five fundamental propositions for future research. The added value of this study lies in the derivation of propositions that not only consider topics for future research as often done in literature reviews, but also with regard to methods, applied theories, and necessary conceptual considerations. Thus, this article is research-oriented and its practical added value arises within the scientific discourse. [...]
Keywords: 650